2014
DOI: 10.1002/cctc.201402524
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Selectivity in the Hydrogenation of Aromatic Ketones Catalyzed by Similar Ruthenium and Rhodium Nanoparticles

Abstract: Scheme 1. Hydrogenation of aromatic ketones.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Instead, the product selectivity of cyclohexyl methyl ketone from 9 was only 20% and 1-phenylethanol (keto group hydrogenation) was observed as the major product, thus indicating preferential reduction of the carbonyl group, instead of ring hydrogenation, for this substrate. 27 Notably, the oxo group contained in benzamide 3 and benzoic acid 4 was not reduced under the applied reaction conditions. These observations corroborate with previously reported results with Rh NPs stabilized on carbon nanofibers (CNF) under similar reaction conditions.…”
Section: Selective Hydrogenation Of Arenes With Rhnps/pvpmentioning
confidence: 99%
“…Instead, the product selectivity of cyclohexyl methyl ketone from 9 was only 20% and 1-phenylethanol (keto group hydrogenation) was observed as the major product, thus indicating preferential reduction of the carbonyl group, instead of ring hydrogenation, for this substrate. 27 Notably, the oxo group contained in benzamide 3 and benzoic acid 4 was not reduced under the applied reaction conditions. These observations corroborate with previously reported results with Rh NPs stabilized on carbon nanofibers (CNF) under similar reaction conditions.…”
Section: Selective Hydrogenation Of Arenes With Rhnps/pvpmentioning
confidence: 99%
“…In another hand, the influence of phosphorus-containing ligands (phosphines [263], [264], phosphites [109], secondary phosphine oxides [265]…),or NHC-carbenes [266] on the reactivity of Ru, Rh or Ir NPs in hydrogenation reactions of arene or carbonyl compounds has been studied by several groups. In particular, it has been observed that the ligand effect on initial rates of aromatic hydrogenation by Ru NPs could be classified in the following order:…”
Section: Influence Of Ligands On Hydrogenation Reactionsmentioning
confidence: 99%
“…Comparison studies between Ru and Rh/phosphine NPs (PPh 3 and Ph 2 P-(CH 2 ) 4 -PPh 2 ) of similar mean sizes regarding hydrogenation of aromatic ketones showed interesting differences in terms of activity and selectivity. The metal-ligand couple is of high importance for the orientation of the catalysis which demonstrates the interest to tailor the surface of NPs to modify their reactivity, as for molecular catalysts [264]. Au NPs are not well-known as hydrogenation catalysts but a recent report showed that the use of a secondary phosphine oxide (SPO) as ligand for the synthesis of Au NPs can have a crucial influence on their catalytic properties leading to excellent results for the chemoselective hydrogenation of a series of substituted aldehydes [112].…”
Section: Influence Of Ligands On Hydrogenation Reactionsmentioning
confidence: 99%
“…The organometallic approach for the synthesis of Rh NPs is not usual in the literature with only a few reports 33,34,35,36,37,38,39,40,41 but its interest to allow fundamental studies in nanocatalysis has been shown.…”
mentioning
confidence: 99%